Impact of Plasticizer Type and Volume on the Properties of Bio-Plastics from Avocado Seed Starch with Chitosan Filler - Susilowati, Susilowati; Putra, Galang Ananda; Ni’am, Hafizh Miftahin; Nurherdiana, Silvana Dwi (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
The starch content in avocado seeds is quite high, which is 79.45% with an amylose content of 29.55% and amylopectin of 49.9%. Avocado seeds contain polyphenols, flavonoids, triterpenoids, quinones, saponins, tannins, monoterpenoids and sesquiterpenoids. The high starch content in avocado seeds allows avocado seeds to be one of the alternative starch sources. The starch content in avocado seeds can be used as a raw material for making bio plastics, thereby reducing the amount of unused avocado seed waste. Bio plastic is an innovation to reduce plastic waste that is difficult to decompose. The main components of bio plastics are hydrocolloids or lipids or composites. Additional materials used in the manufacture of bio plastics are chitosan and plasticizers. Chitosan is useful for improving the tensile strength, elongation, and degradation properties of bio plastics, while plasticizers are useful for increasing the elasticity value of bio plastics. The purpose of this study was to determine the volume ratio of plasticizers and the effect of plasticizer types on the manufacture of bio plastics from avocado seed starch. This research also proves that the type and volume of plasticizer used can successfully produce bio plastics that meet the characteristic testing standards conducted. The results of functional group analysis using FTIR can form O-H bonds in bio plastics among starch, plasticizer and chitosan. Biodegradable results by utilizing soil microorganisms as assistants in the degradation process, bio plastics can be completely degraded for 20 days, as evidenced by perfectly degraded bio plastic sheets in the soil.